A United Description for Dark Matter and Dark Energy - On, Vo Van (Communications in Physics, 2019)
In this paper, we show a unifying description to the dark matter and dark energy. This description does not demand dark energy with the anti-gravitational property. It also points out a lower limit of the average mass of the particles of cosmological energy (ordinary matter, dark matter and dark energy particles) \(m54\) eV. The coincident problem between the density of dark energy and one of matter is a clear fact.